Correlation between the intestinal microflora and peripheral blood Th1/Th2 balance in hypothyroidism during the first half of pregnancy - Wu, Bo; Xu, Yajuan; Ban, Yanjie; Zhang, Miao; Sun, Zongzong; Cai, Yanjun; Li, Jingjing; Hao, Yingqi; Ouyang, Qian; Hu, Lin; Tian, Xin; Liu, Dong (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Objective: This study aimed to investigate the relationship between intestinal microflora characteristics and the peripheral blood T helper cell (Th)1/Th2 balance in patients with hypothyroidism during the first half of pregnancy. Methods: The Th1/Th2 ratios in the peripheral blood of pregnant women in the hypothyroidism and control groups were determined using flow cytometry. The cytometric bead array assay was used to determine the serum levels of interleukin-2 (IL-2), IL-4, IL-6, IL-10, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ. Moreover, 16S rRNA amplicon sequencing was used to determine the intestinal microbial composition in the two groups. Finally, the relationships between intestinal microflora, Th1/Th2 cells, cytokines, and clinical indicators were analyzed. Results: C-reactive protein levels were higher in the hypothyroidism group than in the control group. In contrast to the control group, the hypothyroidism group showed an increase in Th1 cells and the Th1/Th2 ratio, and a decrease in Th2 cells. The hypothyroidism group had higher serum IL-2, TNF-α, and IFN-γ levels, and lower IL-10 levels, than the control group. The richness of the intestinal microflora in the hypothyroidism group increased whereas the diversity decreased. The linear discriminant analysis effect size revealed that the hypothyroidism group had a higher abundance of Prevotella and Faecalibacterium, but a lower abundance of Bacteroides, compared to the control group. Prevotella was positively correlated with Th1 cells, the Th1/2 ratio, and TNF-α. Bacteroides was positively correlated with Th2 cells and IL-10, but negatively correlated with Th1 cells, the Th1/2 ratio, TNF-α, and IFN-γ. The thyroid peroxidase antibody level was directly proportional to TNF-α. Conclusion: A Th1/Th2 imbalance occurs in patients with hypothyroidism during the first half of pregnancy. Disorders of the intestinal microflora may lead to hypothyroidism during pregnancy by affecting the Th1/Th2 balance.